Photorealism in Mixed Reality: A Systematic Literature Review - Pereira, Lidiane; Roberti Junior, Wellingston C.; Silva, Rodrigo L. S. (International Journal of Virtual Reality, 2021)
In Augmented Reality systems, virtual objects are combined with real objects, both three dimensional, interactively and at run-time. In an ideal scenario, the user has the feeling that real and virtual objects coexist in the same space and is unable to differentiate the types of objects from each other. To achieve this goal, research on rendering techniques have been conducted in recent years. In this paper, we present a Systematic Literature Review aiming to identify the main characteristics concerning photorealism in Mixed and Augmented Reality systems to find research opportunities that can be further exploited or optimized. The objective is to verify if exists a definition of photorealism in Mixed and Augmented Reality. We present a theoreticalfundamental over the most used methods concerning realism in Computer Graphics. Also, we want to identify the most used methods and tools to enable photorealism in Mixed and Augmented Reality systems.